Chemical Pressure Boost Record‐High Superconductivity in van der Waals Materials FeSe1−xSx. (10th July 2021) - Sun, Ruijin; Jin, Shifeng; Deng, Jun; Hao, Munan; Zhong, Xin; Ma, Yuxin; Li, Mingxing; Chen, Xiaolong
Abstract: High pressure has become a powerful platform for creating and controlling novel states of matter, including high temperature ( T c ) superconductivity. However, the emergent phenomena generally disappear as high pressure is removed and cloud prospects for future applications. Here, from a distinguishing perspective, FeSe1− x S x is reported as 2D van der Waals materials with extraordinary high‐ T c at ambient pressure, where the superconductivity is boosted by extreme "chemical pressure" inside the materials. Superior to external high pressure, isovalent S substitution in FeSe leads to a much greater compression rate within the superconducting iron‐chalcogenide layer, which guarantees an unabridged superconducting dome that peaked at 37.5 K. Density functional theory calculations reveal that the decreased lattice and structural parameters contribute together for the shift of Fe 3d x 2− y 2 orbital, which creates a new hole‐pocket at the Fermi level that intimately correlated with the enhanced superconductivity. This study demonstrates the design of materials with optimized superconductivity by introducing chemical pressure. Abstract : Physical pressure can drastically increase the transition temperature ( T c ) of many superconductors. This study shows in tetragonal FeSe, a simple 2D van der Waals material, that isovalent atomic substitution can mimic the effect of high‐pressure and boost record‐high superconductivity under ambient conditions.